Studi Kelayakan Pengembangan Ekowisata Pemancingan Kampung Hijrah - Kiky, Andreas (Indonesian Journal for Social Responsibility, 2024)
Hijrah Village is a region in a part of North Panunggangan Ward that needs a community services program to develop an Eco-tourism spot. The program of Eco-tourism starts when the community is very enthusiastic about fishing recreation around the community spot. However, the feasibility of developing a fishing recreation spot has not been studied at this stage. The potency of this fishing spot can be enhanced further by being professionally managed. The purpose of this program is to develop the inhabitants' competencies through workshops and seminars to achieve good governance. The result of this feasibility study of the Eco-tourism fishing spot at Kampung Hijrah based on the NPV method can be considered feasible.